Social Responsibility and Ethics Practices on Purchase Intention of Female Mobile Phone Users in Nigeria - Ajayi; and Ajayi, Omobola; O., Paul (British Journal of Marketing Studies, 2021)
This study examined the effects of social responsibility and ethics practice on purchases intention of female mobile phone users in Ekiti State. The total population for the study was 9495 with the sample of 357 gotten from Krecie and Morgan sample size table. The data were analysed from the information collected through questionnaire. The research makes use of chi-square to check the relationship between the explanatory variables and the dependent variable at 0.05 level of significant. The results revealed that 85% of the respondents totally agreed that social responsibility influence purchase intention among mobile phone users in Ekiti State. While only 5% are undecided and the other 10% of the respondents strongly disagreed with the statement. Therefore, it is clear that social responsibility has an influence on the purchase intention of female mobile phone users in Ekiti State. It was concluded that for any organization to survive, it has to properly take part in social responsibility activity as more women approve of it. The study recommended that company should expand their activities by going into other areas like health, education, charity giving, instead of focusing sport and entertainment.